A randomised controlled trial of an implementation strategy delivered at scale to increase outdoor free play opportunities in early childhood education and care (ECEC) services: a study protocol for the get outside get active (GOGA) trial - Sze Lin Yoong; Nicole Pearson; Kathryn Reilly; Luke Wolfenden; Jannah Jones; Nicole Nathan; Anthony Okely; Patti-Jean Naylor; Jacklyn Jackson; Luke Giles; Noor Imad; Karen Gillham; et al. (BMC, 2022)
Abstract Background Increased outdoor play time in young children is associated with many health and developmental benefits. This study aims to evaluate the impact of a multi-strategy implementation strategy delivered at scale, to increase opportunities for outdoor free play in Early Childhood Education and Care (ECEC) services. Methods The study will employ a parallel-group randomised controlled trial design. One hundred ECEC services in the Hunter New England region of New South Wales, Australia, will be recruited and randomised to receive either a 6-month implementation strategy or usual care. The trial will seek to increase the implementation of an indoor-outdoor routine (whereby children are allowed to move freely between indoor and outdoor spaces during periods of free play), to increase their opportunity to engage in outdoor free play. Development of the strategy was informed by the Behaviour Change Wheel to address determinants identified in the Theoretical Domains Framework. ECEC services allocated to the control group will receive 'usual' implementation support delivered as part of state-wide obesity prevention programs. The primary trial outcome is the mean minutes/day (calculated across 5 consecutive days) of outdoor free play opportunities provided in ECEC services measured at baseline, 6-months (primary end point) and 18-months post baseline. Analyses will be performed using an intention-to-treat approach with ECEC services as the unit of analysis, using a linear mixed effects regression model to assess between-group differences. A sensitivity analysis will be undertaken, adjusting for service characteristics that appear imbalanced between groups at baseline, and a subgroup analysis examining potential intervention effect among services with the lowest baseline outdoor free play opportunities. Discussion Identifying effective strategies to support the implementation of indoor-outdoor routines in the ECEC setting at scale is essential to improve child population health. Trial registration Australian New Zealand Clinical Trials Registry ( ACTRN12621000987864 ). Prospectively registered 27th July 2021, ANZCTR - Registration.